2019
DOI: 10.1590/1982-0224-20190025
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate commercial formulation effects on preoptic area and hypothalamus of Cardinal Neon Paracheirodon axelrodi (Characiformes: Characidae)

Abstract: In Colombia the use of glyphosate commercial formulations (Roundup™) for spraying have left deleterious effects on animals and humans. Much of this spraying takes place at the Orinoco basin, habitat of one of the most exported ornamental fish in Colombia, Cardinal neon. To evaluate the effect of Roundup Activo™ four experimental treatments were carried out with 0 mg/L (T1), 0.1 mg/L (T2), 1 mg/L (T3) and 5 mg/L (T4) during 30 days of exposure. The fishes were processed for high-resolution optical microscopy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Another two sh were xed in Karnovsky and post-xed in 2.5% osmium tetroxide for high-resolution optical microscopy (HROM) and transmission electron microscopy (TEM). Subsequently, samples were dehydrated with a series of ethanol solutions at increasing concentrations (70%, 80%, 90%, and 100%), embedded in Poly/Bed 812® resin sectioned at 1mm with a rotary microtome (CUT SLEE 4060®), and stained with toluidine blue (Riaño et al, 2019). For ultrastructure analysis by TEM, tissue samples were sectioned into ultrathin 150 nm sections using ultramicrotome Leica® EM UC6.…”
Section: Processing Of Tissues For Light and Transmission Electron Mi...mentioning
confidence: 99%
“…Another two sh were xed in Karnovsky and post-xed in 2.5% osmium tetroxide for high-resolution optical microscopy (HROM) and transmission electron microscopy (TEM). Subsequently, samples were dehydrated with a series of ethanol solutions at increasing concentrations (70%, 80%, 90%, and 100%), embedded in Poly/Bed 812® resin sectioned at 1mm with a rotary microtome (CUT SLEE 4060®), and stained with toluidine blue (Riaño et al, 2019). For ultrastructure analysis by TEM, tissue samples were sectioned into ultrathin 150 nm sections using ultramicrotome Leica® EM UC6.…”
Section: Processing Of Tissues For Light and Transmission Electron Mi...mentioning
confidence: 99%
“…11,18 It has been reported that the number of mastocytes increased in the preoptic area of the adult fish Paracheirodon axelrodi after exposure to a Roundup ® solution containing 1-5 mg/L glyphosate. 15 In tadpoles, after exposure to glyphosate formulations (0.21 mg/L), changes in metamorphosis were observed as well as a diminished brain THR alpha and beta expression and an increased Dio2/Dio3 expression were also reported. 19 In adult rats, diminished levels of follicle stimulating hormone and testosterone coupled to increased levels of luteinizing hormone and estrogens have been reported after glyphosate exposure (400 or 2000 mg/kg/day).…”
Section: Introductionmentioning
confidence: 95%
“…1,[12][13][14] Pesticides, including glyphosate-based herbicides, have been widely used in agriculture for weed control, grain drying and fumigation of transgenic crops. [15][16][17] Data, obtained from several vertebrate species, strongly indicate that glyphosate and its commercial formulations act as endocrine disruptors by altering the hypothalamic-pituitaryendocrine axis. For example, the levels of key molecules involved in reproductive mechanisms are altered to different degrees.…”
Section: Introductionmentioning
confidence: 99%